Infectious Sporozoites of Plasmodium berghei Effectively Activate Liver CD8α+ Dendritic Cells - Parmar, Rajesh; Patel, Hardik; Yadav, Naveen; Parikh, Ritika; Patel, Khyati; Mohankrishnan, Aditi; Bhurani, Vishakha; Joshi, Urja; Dalai, Sarat Kumar (Frontiers in Immunology, 2018)
Immunization with radiation-attenuated sporozoites (RAS) shown to confer complete sterile protection against Plasmodia liver-stage (LS) infection that lasts about six to nine months in mice. We have found that the intermittent infectious sporozoite challenge to immune mice following RAS vaccination extends the longevity of sterile protection by maintaining CD8+T cell memory responses to LS infection. It is reported that CD8α+DCs are involved in the induction of LS specific CD8+T cells following RAS or genetically attenuated parasite (GAP) vaccination. In this study, we demonstrate that CD8α+DCs respond differently to infectious sporozoite or RAS inoculation. The higher accumulation and activation of CD8α+DCs was seen in the liver in response to infectious sporozoite 72 hr post inoculation, and found to be associated with higher expression of chemokines (CCL-20 and CCL-21) and Type-I interferon response via Toll-like receptor (TLR) (Toll-like receptor) signalling in liver. Moreover, the infectious sporozoites was found to induce qualitative changes in terms of the increased MHCII expression as well as co-stimulatory molecules including CD40 on the CD8α+DCs compared to RAS inoculation. We have also found that infectious sporozoite challenge increased CD40L expressing CD4+T cells, which could help CD8+T cells in the liver through ‘licensing’ of the APCs. Our results suggest that infectious sporozoite challenge to prior RAS immunized mice modulates the CD8α+DCs, which might be shaping the fate of memory CD8+T cells against Plasmodium LS infection.